Nature of Bonding in Donor–Acceptor Interactions Exemplified by Complexes of N‐Heterocyclic Carbenes with 1, 2, 5‐Telluradiazoles. Issue 46 (31st July 2017) - Pushkarevsky, Nikolay A.; Petrov, Pavel A.; Grigoriev, Denis S.; Smolentsev, Anton I.; Lee, Lucia M.; Kleemiss, Florian; Salnikov, Georgy E.; Konchenko, Sergey N.; Vargas‐Baca, Ignacio; Grabowsky, Simon; Beckmann, Jens; Zibarev, Andrey V.
Abstract: Comprehensive structural, spectroscopic, and quantum chemical analyses of new donor–acceptor complexes between N‐heterocyclic carbenes and 1, 2, 5‐telluradiazoles and a comparison with previously known complexes involving tellurenyl cations showed that the dative C−Te bonds cannot be solitarily described with only one Lewis formula. Canonical Lewis formulas that denote covalency and arrows emphasizing ionicity complement each other in varying extents. Evaluation of the relative weights of these resonance forms requires proper bonding description with a well‐balanced toolbox of analytical methods. If for conciseness only, one resonance form is used, it must be the most significant one according to the analytical evaluation. If unclear, all significant resonance forms should be displayed. Abstract : My name is Bond : Comprehensive structural, spectroscopic, and quantum chemical analyses of new donor–acceptor complexes between N‐heterocyclic carbenes and 1, 2, 5‐telluradiazoles and a comparison with previously known complexes involving tellurenyl cations showed that the dative C−Te bonds cannot be solitarily described with only one Lewis formula (see scheme).